Suscetibilidade magnética de argissolos sob usos agrícolas e natural no sul do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
With the improvement of agriculture, there is an increasing demand for quick and detailed information on soil attributes, to assist in agricultural and political decision-making, in addition to supporting sustainable production. However, obtaining more detailed levels of information requires more samples, resources and processing time. Magnetic Susceptibility (SM) measurements as an environmental proxy can be an alternative to circumvent these obstacles, as its use allows the evaluation of physical and chemical soil attributes in a simple, fast, without environmental impact and relatively low cost way. Therefore, this work aimed to characterize the magnetic susceptibility in Argissolos under uses natural and agricultural in the south of Amazonas, to investigate its use as a proxy and to provide practical applications for evaluating soil attributes from its use. The study was developed within the São Francisco Settlement Project located in the municipality of Canutama, AM. Four areas were selected, three areas under different crops: Annatto, Cupuaçu, Guarana and more forest area (reference). Meshes were established according to the dimensions of the cultivation, so that the collection of samples at the crossing points of the meshes resulted in 64 samples per area. Sampling was done at three depths, 0.00-0.05, 0.05-0.10, and 0.10-0.20 m, giving 192 samples per area and totaling 768 samples. The points were georeferenced with a GPS device. Then, physical, chemical and fertility analyzes were performed to obtain the values of the soil attributes. The SM was determined using the Bartington Instrument to obtain the specific mass SM (χ) in three reading frequencies: low (χlf), high (χhf), and dependent (χfd). Then, descriptive statistics, ANOVA, geostatistics and MANOVA were applied to characterize χ in southern Amazonas. In the first study, the results show that the conversion of natural Argisols to agricultural crops directly implied an increase in the density and amplitude of the pH in water and Al3+ of the soil, and in the reduction of macroporosity, gravimetric humidity, available phosphorus and iron oxalate contents, and the incorporation of organic carbon in depth. However, all Argisols have characteristically low values of χlf and χhf due to the low concentration of iron oxides with low χ, and undergo high superparamagnetic improvement, probably due to the pedogenic processes, intense weathering, favorable climate and high presence of diamagnetic that interfere with your measurement. However, χ measurement frequencies were correlated with the fertility and texture attributes, meaning that its use can be used as an adequate proxy for monitoring the fertility of Argissolos grown in southern Amazonas. In the second study, all χ frequencies were shown to be spatially correlated and with the presence of anisotropy. Then, the anisotropic correction improved the parameters of the spatial correlation models, together with the thematic maps generated by χ kriging. These maps should, therefore, be used as indicators of their variability in the soil, paying special attention mainly in research related to the delimitation of specific management zones.
Keywords: Pesquisa agrícola; Anisotropia; Solos - Análise; CIÊNCIAS AGRÁRIAS: AGRONOMIA: CIÊNCIA DO SOLO: GENESE, MORFOLOGIA E CLASSIFICAÇÃO DOS SOLOS; CIÊNCIAS AGRÁRIAS: AGRONOMIA: CIÊNCIA DO SOLO: FÍSICA DO SOLO; Conversão agrícola; Óxidos de ferro; Krigagem; Proxy; Anisotropia